La politique populaire a-t-elle un genre ? Un exemple mexicain - Matthew C. Gutmann (Cahiers des Amériques Latines)
This article is based on the ethnographic study of a popular area of the town of Mexico, the colonia Santo Domingo, founded thirty years ago by ‘invadors’. In using the example of the presidential elections in Mexico in 1988, 1994 and 2000, we observe that in Santa Domingo over the last twenty years, men and women have envisaged the elections and the popular urban movements as men and women, with different dreams for improving their lives and society, and of being cultural citizens.